Exergy analysis of a biorefinery process for co-production of third-generation L-lactic acid and electricity from Eucheuma denticulatum residues. (1st March 2022) - Chung, Millicent Rosette Wan Yi; Tan, Inn Shi; Foo, Henry Chee Yew; Lam, Man Kee
Abstract: This paper evaluates the thermodynamic performance of three different l-lactic acid (LLA) biorefinery scenarios, utilizing macroalgae cellulosic residue, namely Eucheuma denticulatum residues (EDRs), as raw materials. To establish exergy analysis, the thermodynamic properties of each biorefinery scenario was obtained through process simulation using Aspen Plus® V10. It was found that microwave-assisted autohydrolysis (MAA) was feasible in minimizing the amount of EDRs needed by 70.2% to produce 1000 kg/h of LLA. The fermentation unit, wastewater treatment (WWT) unit, and combined heat and power (CHP) unit were ranked top three for the occurrence of exergy destruction. Both the LLA recovery unit (99.37%) and MAA pretreatment unit (99.68%) were found to be highly exergetically efficient. Among the three scenarios, Scenario III, which was integrated with power generation and a proper waste management system, had the highest functional exergy efficiency (22.12%) and normalized exergy destruction (0.73). It demonstrated the highest functionality due to the prevention of material losses by converting waste streams into value-added products and reducing reliance on fossil-fuel derived energy for plant operation. The valuable information from exergy analysis provides theoretical guidance for performance enhancement in a macroalgae-based biorefinery to produce LLA, either with process integration or technology advancement. Graphical abstract: Image 1 Highlights: l-lactic acid production from macroalgae waste was evaluated thermodynamically. Raw materials and energy demand were reduced with MAA pre-treatment. PSSF subunit exhibited the highest exergy losses in all biorefinery scenarios. Scenario III had the highest functional exergy efficiency of 22.12%. The normalized exergy destruction of Scenario III was determined as 0.73.